Reimagining Urban Public Spaces: A Study of Spatial Rights and Community Interaction in Jabal Al-Hussein, Jordan - Alkhreasat, Ayat; Suleiman, Sarinaz (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2025)
The paramount determinant of open space's success lies in the harmonious fusion of its design and environmental context. Considering people's environmental experience is crucial for implementing user-friendly spatial planning. This can be achieved by acknowledging the concept of